2021
DOI: 10.22435/jtoi.v14i1.4301
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH ELISITOR KITOSAN TERHADAP KANDUNGAN WITHANOLID TUNAS IN VITRO AKSESI TANAMAN Physalis angulata DARI PULAU MADURA

Abstract: ABSTRACT Chitosan is often applied to in vitro culture systems to induce the biosynthesis of a plant's secondary metabolites. The accumulation and profile of secondary metabolites of the same plant species growing in different environments can vary. This study aims to identify and measure withanolide compounds of in vitro shoots of Physalis angulata accessions. Samples obtained from three regions in Madura Island, namely Sampang (A1), Sumenep (A2 and A4), and Pamekasan (A5). Withanolide compounds of in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The diversity of secondary metabolites is determined by various factors, such as genetics, age, season at harvest time, environmental fluctuations, soil conditions, and biochemical interactions between competing plants, that may regulate the synthesis of various secondary metabolites. (22,23) In addition, the solvents used for extracting the processed materials and the drying method (sun-, air-, or oven-drying) can also cause quantitative changes in the composition of the phytochemical compounds. (21) The quantity of the metabolites is also affected by the location or origin of the PA. Akomolafe et al (24) from Nigeria reported that the most abundant type of flavonoid found in PA leaf extract is quercetin at 56.74 mg/g.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of secondary metabolites is determined by various factors, such as genetics, age, season at harvest time, environmental fluctuations, soil conditions, and biochemical interactions between competing plants, that may regulate the synthesis of various secondary metabolites. (22,23) In addition, the solvents used for extracting the processed materials and the drying method (sun-, air-, or oven-drying) can also cause quantitative changes in the composition of the phytochemical compounds. (21) The quantity of the metabolites is also affected by the location or origin of the PA. Akomolafe et al (24) from Nigeria reported that the most abundant type of flavonoid found in PA leaf extract is quercetin at 56.74 mg/g.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of withanolide profiles begins with phytochemical screening and identification of withanolides using LC-MS [28].…”
Section: Analysis Of Withanolide Content By Hplc Methodsmentioning
confidence: 99%